Cheater-altruist synergy in public goods games. (7th October 2018) - Morsky, Bryce; Vural, Dervis Can
Highlights: Six models of cancer growth with a public goods game under immune system suppression are explored. We show how cheaters are beneficial to the population as a whole. Under a linear benefit function, the cancer cells face a threshold Volunteers Dilemma whereby a threshold of cooperation is required to escape immune system suppression. Under the nonlinear Monod function, optimal growth of the tumor occurs for a mixture of altruists and cheaters. Abstract: Much research has focused on the deleterious effects of free-riding in public goods games, and a variety of mechanisms that suppress cheating behavior. Here we argue that under certain conditions cheating can be beneficial to the population. In a public goods game, cheaters do not pay for the cost of the public goods, yet they receive the benefit. Although this free-riding harms the entire population in the long run, the success of cheaters may aid the population when there is a common enemy that antagonizes both cooperators and cheaters. Here we study models of the interactions between tumor cells, which play a public goods game, and the immune system. We investigate three population dynamics models of cancer growth combined with a model of effector cell dynamics. We show that under a public good with a limiting benefit, the presence of cheaters aids the tumor in overcoming immune system suppression, and explore the parameter space wherein it occurs. The mechanism of this phenomenon is that a polymorphism of cheaters and altruists optimizes the average growth rate of the tumor, which is what determines whether or not the immune response is overcome. Our results give support for a possible synergy between cooperators and cheaters in ecological public goods games.